2011
DOI: 10.1016/j.jacc.2010.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Method to Derive Central Aortic Systolic Pressure From the Radial Pressure Waveform Using an N-Point Moving Average Method

Abstract: We show that an NPMA with a denominator of one-quarter of the tonometer sampling frequency accurately defines CASP when applied to noninvasively acquired RAPWFs in man. These novel findings have important implications for the simplification of noninvasive CASP measurement and its wider application in clinical trials and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 34 publications
5
118
1
2
Order By: Relevance
“…To this we may add the slight underestimation of CASP with SphygmoCor vs. the invasive method, as has already been reported by other authors 22,23 -a situation that does not appear to occur with B-Pro. 12 Williams et al 12 The correlation found between the two measurements of CASP (r¼0.94, Po0.01) was also similar to that reported by Williams et al, depending on the method employed (r¼0.95 or r¼0.99). However, the intraclass correlation in this study was intermediate between the two (r¼0.97, 95%CI: 0.96-0.98)-thus indicating that the measures may be inter-exchangeable.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…To this we may add the slight underestimation of CASP with SphygmoCor vs. the invasive method, as has already been reported by other authors 22,23 -a situation that does not appear to occur with B-Pro. 12 Williams et al 12 The correlation found between the two measurements of CASP (r¼0.94, Po0.01) was also similar to that reported by Williams et al, depending on the method employed (r¼0.95 or r¼0.99). However, the intraclass correlation in this study was intermediate between the two (r¼0.97, 95%CI: 0.96-0.98)-thus indicating that the measures may be inter-exchangeable.…”
Section: Discussionsupporting
confidence: 79%
“…Central blood pressure was measured with Pulse Wave Application Software (B-Pro+A-Pulse software; HealthSTATS International) using tonometry attached to a wrist (like a wristwatch) to record the radial pulse with the patient in the sitting position and resting the arm on a firm surface, using an equation to estimate CASP. 12 The increases in central blood pressure, mean blood pressure and rAIx were estimated as well. rAIx was calculated from the radial wave pulse as follows: (second peak SBP (SBP2)ÀDBP)/(first peak SBPÀDBP)Â100, 13 as seen in Figure 1.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This tonometric method has been validated against the gold standard of direct aortic root measurement during cardiac catheterisation, with excellent correlation (r = 0.99). (9) A recent study involving patients with type I diabetes mellitus also showed that there was good agreement between the CASP readings measured using both the SphygmoCor and BPro devices; (10) i.e. any differences observed were within the acceptable limits recommended by the Association for the Advancement of Medical Instrumentation (AAMI) and the European Society of Hypertension (ESH).…”
Section: Introductionmentioning
confidence: 89%
“…(7) The BPro watch, developed by Dr Ting Choon Meng, a Singaporean doctor and an inventor of medical devices, was validated to accurately measure CASP. (8) This study is important to the cardiology community, as CASP has been shown to predict cardiovascular events better than brachial blood pressure. (9) Moreover, ARBs are thought to act more favourably on CASP than other classes of antihypertensive drugs, albeit only in Western populations.…”
mentioning
confidence: 99%